Analisis Semioika Dalam Iklan Politik Gerindra “Sarjana Kerja Kerja Kerja!” - Herman Herman (Institut Agama Islam Negeri Kendari, 2019)
Gerindra Party's political advertisement, which was viral several weeks ago, caused controversy among netizens. Where the ad was posted on the @Gerindra account on its Twitter page on December 14th. This becomes interesting to study, so that the writer is able to interpret the signs in the ad. The cause of the viral advertisement is the content carried by carrying the icon of the profession